IMMUNOHISTOCHEMICAL MARKERS IN THE DIAGNOSIS OF PRECANCEROUS LESIONS OF THE ORAL MUCOSA - Y. G. Kolenko; O. V. Kalenskaya (Bogomolets National Medical University, 2016)
The study included 155 patients with clinical diagnosis of leukoplakia of the oral mucosa. 52 (33.6%) had a flat form, 40 (25.8%) - increased form, 43 (27.7%) - warty and 20 (12.9%) erosive and ulcerative form of leukoplakia. There were 10 (14%) sites intact mucosa, 10 (14%) of hyperkeratosis samples without atypia, 14 (19%) biopsies with hyperkeratosis SIN1, 15 (21%) with hyperkeratosis SIN2, 10 (14%) - SIN3 and 13 (18 %) of cases of squamous cell carcinoma. In assessing the proliferative activity of mucosal epithelial cells of the oral cavity the proliferation index (PI Ki-67) is used, which is determined in each cell a number unchanged epithelium, with leukoplakia (without atypia, SIN1, SIN2, SIN3) and squamous cell carcinoma of the oral mucosa. We have found that with the overall increase in the proliferative activity of epithelial cells with the growth of SIN, for each study group is characterized by the distribution of proliferating cells in the thickness of the epithelium. This allows you to make a differential diagnosis between the types of leukoplakia and squamous cell carcinoma of GPRS. To determine the degree of epithelial neoplasia in the early diagnosis of malignant transformation of cells must take into account the distribution imunopositive cells in the basal and parabasal layers.